INFORMATION SECURITY IN MECHATRONIC SYSTEMS - Киричук, Юрий; Назаренко, Наталія; Заєць, Сергій (Modern engineering and innovative technologies, 2024)
The work considers the ways of ensuring information security in mechatronic systems. Ensuring the information security of mechatronic systems is critically important for maintaining their functionality, reliability and security. Taking into account the s